Efficacy of Breast Milk Booster Supplement (BBS) on Breast Milk Volume and Nutrient Content: A Single-Blind Randomized Controlled Trial - Trias Mahmudiono; Qonita Rachmah; Azizah Ajeng Pratiwi; Dayinta Annisa Syaiful; Alinda Rahmani; Eka Anisah Yusryana; Natasya Ayu Andamari; Asri Meidyah Agustin (Universitas Airlangga, 2026)
Background: Natural galactagogues are widely used to support lactation, but evidence for their effectiveness remains limited. This study evaluated the effects of a breast milk booster supplement (BBS) containing Moringa oleifera, Channa striata, and Sauropus androgynus on breast milk volume and nutrient composition. Methods: In this single-blind randomized controlled trial, 77 lactating mothers were assigned to receive either BBS or a placebo. Expressed breast milk volume and nutrient composition were assessed at baseline, day 7, and day 28. Nutrient analyses included energy, protein, carbohydrate, calcium, and omega-3 fatty acids, including docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). Data were analyzed using the Mann-Whitney and Greenhouse-Geisser repeated-measures tests. Results: The intervention group showed a greater increase in expressed breast milk volume than the control group (348.6 vs. 281.8 mL; p=0.016). EPA concentration was significantly higher at day 28 (3.2 mg/100 g; p=0.027). Although DHA and calcium increased to a greater extent in the intervention group, the differences were not statistically significant. Infants in the intervention group also had significantly greater increases in mid-upper arm circumference (MUAC). Conclusion: Twenty-eight days of BBS supplementation increased expressed breast milk volume and EPA content, supporting its potential as a lactation supplement.